El proceso formativo del estudiante con necesidades educativas especiales, (nee), en la universidad técnica de Cotopaxi. Propuesta de capacitación del docente universitario para la educación inclusiva y el diseño de adaptaciones curriculares. - Molina Proaño, Johanna Elizabeth (2016)
The present research arose by the need to clear the following uneasiness: How does the training of university teachers incise into the professional training with special educational needs associated to the disability at the Technical University of Cotopaxi. Therefore, the main purpose was to propose training modulus in inclusive education and curricular adaptation design for university teacher, with the latest goal of favoring the training process of students with special educational needs associated to the disability at the Technical University Cotopaxi. The hypothesis, which guided the research was directed to verify the incidence of the university teacher training for inclusive education, the training process of the students with special educational needs. In order to achieve the objective and to verify the hypothesis are performed an analysis of recent educational theories in the current context. Consecutively, we proceeded to perform field research, in order to diagnose the actual situation of the university teacher training and curricular adaptation in the university classroom. The research design started from a mixed approach of quantitative-qualitative character. Techniques are used for the collection of information such as interview and survey. As main results, it was verified the shortcomings existence in the professional formation of the student. Besides, it was evidenced a minimum percentage of students with special educational needs which manifests the need to develops more inclusive spaces in the University. Finally, an alternative solution was constitute through the design of training for the university teacher defining some competences of the inclusive university teacher and strategies for the curricular adaptations design.